2020
DOI: 10.1371/journal.pone.0231967
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virus-neutralising antibodies and associated factors against rabies in the vaccinated household dogs of Kathmandu Valley, Nepal

Abstract: BackgroundRabies is a vaccine-preventable neglected tropical viral zoonosis. It occurs worldwide, creating a very heavy burden in many developing countries, including Nepal. Dogs are the principle vector for the transmission of this disease in urban areas. Vaccination is the most important preventive measure in areas where dogs are the principle source of infection. This study was conducted with the aim of detecting virus-neutralising antibodies and associated factors against rabies in vaccinated household dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…found no differences between the two types of vaccines. 48 We also found higher titers in dogs vaccinated in public mass vaccination campaigns than dogs vaccinated at private veterinary clinics ( P = 0.005). This may be related to the type of vaccine used; in Peru, single-pathogen vaccines are used in mass dog vaccination campaigns, whereas combined-pathogen vaccine are commonly used in private veterinary clinics.…”
Section: Discussionmentioning
confidence: 54%
“…found no differences between the two types of vaccines. 48 We also found higher titers in dogs vaccinated in public mass vaccination campaigns than dogs vaccinated at private veterinary clinics ( P = 0.005). This may be related to the type of vaccine used; in Peru, single-pathogen vaccines are used in mass dog vaccination campaigns, whereas combined-pathogen vaccine are commonly used in private veterinary clinics.…”
Section: Discussionmentioning
confidence: 54%
“…In this study 60% of vaccinated dogs showed inadequate protective levels of titres within the year of last rabies vaccination in 180 vaccinated dogs in Chennai, India. This proportion is far higher than other reports from similar studies 40–42 . This is not only a concern for rabies control efforts in the canine population but also increases the risk of rabies in humans who may not seek post‐exposure prophylaxis after a bite from a vaccinated dog.…”
Section: Discussionmentioning
confidence: 76%
“…This proportion is far higher than other reports from similar studies. [40][41][42] This is not only a concern for rabies control efforts in the canine population but also increases the risk of rabies in humans who may not seek post-exposure prophylaxis after a bite from a vaccinated dog. It is crucial that vaccines selected for use by the veterinary public sector and for mass dog vaccination campaigns are of high quality and retain potency until administration.…”
Section: Discussionmentioning
confidence: 99%
“…Berbagai faktor telah dilaporkan memengaruhi pembentukan antibodi rabies pada anjing adalah usia anjing, ras, jenis vaksin, kedaluwarsa vaksin, kualitas vaksin selama vaksinasi massal (cold chain) (Rimal et al, 2020), keterampilan vaksinator, aplikasi vaksin, dosis vaksin, dan monitoring vaksinasi (Suardana, 2014).…”
Section: Pendahuluanunclassified